Geochemical data from batch experiments simulating hydrothermal troctolite alteration at 300 and 400°C (40 MPa) - Christian T Hansen; C Johan Lissenberg; Wolf-Achim Kahl; Wolfgang Bach (PANGAEA, 2022)
Troctolites represent a close analogue to komatiites, a type of rock assumed to have been common on ancient earth and thus associated water-rock reactions likely have been important in buffering ancient ocean chemistry including the earliest environments linked to the emergence of life. Hydrothermal alteration of olivine-rich troctolite was investigated in two laboratory experiments (300°C and 400°C, 40 MPa, 1800 hrs). Forsteritic olivine (Fo91) and anorthite-rich plagioclase (An95) at a mass ratio of 3.5 were reacted with a sodium-chlorite solution (3.2 wt.-% NaCl) at a water-rock ratio between 3.3 and 2.4. Reaction progress and the nature of the occurring alteration was evaluated based on concomitant fluid samples. Major elemental loads (magnesium, aluminum, silica, calcium, sodium via Inductively Coupled Plasma Optical Emission Spectroscopy) were analyzed alongside pH, salinity and concentrations of dissolved gases hydrogen and methane (gas chromatography). In-situ pH at reaction conditions was reconstructed via EQ3/6 thermodynamic modeling based on fluid chemistry. Following an initial spike, magnesium is increasingly buffered at low levels in both experiments. Calcium experiences an even higher initial spike but is eventually leveling at high levels. Silica is buffered at exceptionally low levels at 300°C but at comparably high level at 400°C. Simultaneously, pH during the reaction is alkaline at 300°C but neutral or slightly acidic at 400°C. Both experiments produce mmol/L concentrations of hydrogen (H2), but considerably more H2 is formed at 300°C. Methane (CH4) formation is very limited but considerably higher at 400°C and at the higher temperature, both, H2 and CH4 levels decrease towards the termination of the experiments.